International assignments – extending an organizational value framework. Issue 2 (3rd June 2020) - Renshaw, Phil St John; Parry, Emma; Dickmann, Michael
Abstract : Purpose: This study aims to present a framework relating to the organizational value of international assignments (IAs). This extends the existing framework by Lepak et al. (2007) and applies to other fields researching questions of value. Design/methodology/approach: This is a conceptual paper that applies new thinking to the critical practical and theoretical issue of organizational value in global mobility (GM) and international business (IB) literature. The Lepak et al. (2007) framework is explained, used and extended to appraise the value of IAs to organizations. Findings: The primary contribution is the establishment of a value framework within which future IA research can position itself, refining extant measures and thereby enabling greater cohesion in future studies. The secondary contribution, impacting beyond the field of GM, is the development of this framework, including the identification and discussion of value itself, the significance of organizational sub-levels, the extension of the definitions of isolating mechanisms and competition to explicate value capture, the importance of temporal analysis and the inclusion of value assessment. Research limitations/implications: The paper is limited by its application to IAs at the organizational level only. However, the relationship with other levels is also explored. Research within different contexts or focusing on the other levels of value will increase the understanding of value. Practical implications: Definitions of the value of IAs are extended, and practitioner implications are discussed. Originality/value: A new framework for evaluating the organizational value of IAs and new definitions to enable this value to be assessed are produced.